Consumer control and abiotic stresses constrain coastal saltmarsh restoration. (15th November 2020) - Liu, Zezheng; Fagherazzi, Sergio; Ma, Xu; Xie, Chengjie; Li, Jin; Cui, Baoshan
Abstract: Die-off of coastal wetlands has been reported worldwide. Planting habitat-forming species is an important strategy to reverse the decline of coastal wetlands. However, how abiotic environmental stresses and consumers affect the establishment of the planted vegetation species is unclear. We reported a large-scale restoration project in the Liaohe estuary, China, where native pioneer plant Suaeda salsa was planted. We evaluated the growth performance of the planted S. salsa, and identified the constraints on the establishment of planted S. salsa . Results showed that the growth performance (density, coverage and survival rate) of planted S. salsa was better in the low restored marsh than that in the high restored marsh. The death of planted S. salsa was primarily driven by crab herbivory, followed by abiotic stresses (low soil moisture and high salinity) in the high restored marsh, whereas plant death was only driven by crab herbivory in the low restored marsh. Herbivory strength in the high marsh was significantly higher than that in the low marsh. Our findings challenge the bottom-up paradigm used as the foundation for coastal restoration, and highlight the overlooked role of consumers. Therefore, protection measures against consumer pressure, especially in physically harsh conditions, should be considered to enhance the success of coastal wetland restoration. Highlights: China's largest coastal saltmarsh plantation project was initiated in the Liaohe Estuary. The restoration effect of planted Suaeda salsa was better in the low restored site than that in the high restored site. The death of planted Suaeda is primarily driven by herbivory, followed by abiotic stresses in the high restored site. Consumer control should be considered to enhance the success of coastal restoration.